6-5х(под корнем)=х
Возводим обе части в квадрат.
6-5х=х²
6-5х-х²=0
-х²-5х+6=0
Умножим на -1
х²+5х-6=0
х1,2=(-b+-√D)/2a
D=b²-4ac=5²-4*1*(-6)=25+24=49
√49=7
x1=(-5-7)/2*1=-12/2=-6
x2=(-5+7)/2=2/2=1
1=1
6=-6
х=1
х≠-6
х=1
1)12:1 5/7=7(2ой пролет)
2)12*1 7/12=19(3ий пролет)
3)12+7+19=28
180720 / 90
<u>180</u> 2008
720
<u>720</u>
0
2008
* <u> 90</u>
180720
242100 / 30
<u>240</u> 8070
210
<u>210 </u>
0
8070
* <u> 30</u>
242100
818000 /200
<u>800</u> 4090
1800
<u>1800</u>
0
4090
* <u> 200</u>
818000
Ты начало не сфотографировал(а)